Implementation of pulse oximetry measurement to wireless biosignals probe - Jagelka, M; Jeleň, Michal; Vavrinský, Erik; Daříček, Martin; Donoval, Martin (Lékař a technika, 2014)
Monitoring of heart rate variability (HRV) and oxygen saturation is important in medicine as well as training of top athletes. Our work describes the implementation of pulse oximetry functions in sensor system for measurement of biosignals. It allows us to follow along even pulse biosignal and the flow rate of blood.
Keywords: Wireless Technology; oxymetrie; biosenzitivní techniky; Humans; bezdrátová technologie; Signal Processing, Computer-Assisted; lidé; Oximetry; počítačové zpracování signálu; Biosensing Techniques